Exploring Supply Chain Risk Factors for Supplier Selection in Electrical and Electronic Industry in Thailand: A Case Study Approach - Sittichok Sinrat; Walailak Attihirawong (My University, 2014)
Currently, supply chain management is a several organizations and supplier selection is the most important in the success of firms.Therefore, company r supply chain for risk diversification.The risk in supply chain is a potential variation of outcomes, which decreases the efficiency in operations.This paper explores risk factors supplier selection in electrical and electronic industry Results of this study help to understand the important factors for supplier selection.The analysis of risk factors indicate factors highly impact to supply chain management findings can help practitioners to understand risk factors order to manage supply chain more effectively and efficiently
Keywords: Supply Chain Resilience and Risk Management